2004
DOI: 10.1007/s00438-004-1060-2
|View full text |Cite
|
Sign up to set email alerts
|

Flutolanil and carboxin resistance in Coprinus cinereus conferred by a mutation in the cytochrome b 560 subunit of succinate dehydrogenase complex (Complex II)

Abstract: A gene that confers resistance to the systemic fungicide flutolanil was isolated from a mutant strain of the basidiomycete Coprinus cinereus. The flutolanil resistance gene was mapped to a chromosome of approximately 3.2 Mb, and a chromosome-specific cosmid library was constructed. Two cosmid clones that were able to transform a wild-type, flutolanil-sensitive, strain of C. cinereus to resistance were isolated from the library. Analysis of a subclone containing the resistance gene revealed the presence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 32 publications
2
52
0
1
Order By: Relevance
“…2) (35, 59). Mutations in sdhC were previously found in several laboratory and field mutants (29,39,62). Moreover, a recent report indicated that the H134R mutation is prevalent in SdhC of A. alternata collected from pistachios (65).…”
Section: Discussionmentioning
confidence: 91%
“…2) (35, 59). Mutations in sdhC were previously found in several laboratory and field mutants (29,39,62). Moreover, a recent report indicated that the H134R mutation is prevalent in SdhC of A. alternata collected from pistachios (65).…”
Section: Discussionmentioning
confidence: 91%
“…[9] The carboxamides block the energy production in the fungal cells, by inhibiting the succinate ubiquinone reductases containing sulphur. [10] In most grapevine growing areas, populations of B. cinerea resistant to benzimidazoles and/or dicarboximides are widespread, [11] but their incidence is decreasing, thanks to the introduction of anilinopyrimidines and phenylpyrroles that provide good levels of disease control. [12] The availability of novel classes of compounds does not imply the total replacement of the older fungicides, but represents a new powerful tool for the growers.…”
Section: Introductionmentioning
confidence: 99%
“…The primary target of the SDHI fungicides is the SDH complex that consists of four subunits: a flavoprotein (Fp) subunit (SdhA), an iron-sulfur protein (Ip) subunit (SdhB), and two membrane-anchored protein subunits (SdhC and SdhD). Mutations conferring resistance have been found in the SDHB (Avenot et al 2008) and SDHC (Ito et al 2004) and SDHD subunits (Avenot et al 2009). …”
Section: Sdhimentioning
confidence: 99%